Earthen plasters based on illitic soils from Barrocal region of Algarve: contributions for building performance and sustainability - Lima, José (2016)
Clayish earth-based mortars can be considered eco-efficient products for indoor plastering since they can contribute to improve important aspects of building performance and sustainability. Apart from being products with low embodied energy when compared to other types of mortars used for interior plastering, mainly due to the use raw clay as natural binder, earth-based plasters may give a significant contribution for health and comfort of inhabitants. Due to high hygroscopicity of clay minerals, earth-based mortars present a high adsorption and desorption capacity, particularly when compared to other type of mortars for interior plastering. This capacity allows earth-based plasters to act as a moisture buffer, balancing the relative humidity of the indoor environment and, simultaneously, acting as a passive removal material, improving air quality. Therefore, earth-based plasters may also passively promote the energy efficiency of buildings, since they may contribute to decreasing the needs of mechanical ventilation and air conditioning. This study is part of an ongoing research regarding earth-based plasters and focuses on mortars specifically formulated with soils extracted from Portuguese ‘Barrocal’ region, in Algarve sedimentary basin. This region presents high potential for interior plastering due to regional geomorphology, that promote the occurrence of illitic soils characterized by a high adsorption capacity and low expansibility. More specifically, this study aims to assess how clayish earth and sand ratio of mortars formulation can influence the physical and mechanical properties of plasters. For this assessment four mortars were formulated with different volumetric proportions of clayish earth and siliceous sand. The results from the physical and mechanical characterization confirmed the significantly low linear shrinkage of all the four mortars, as well as their extraordinary adsorption-desorption capacity. These results presented a positive correlation with mortars´ clayish earth content and are consistent with the mineralogical analysis, that confirmed illite as the prevalent clay mineral in the clayish earth used for this study. Regarding mechanical resistance, although the promising results of the adhesion test, the flexural and compressive strength results suggest that the mechanical resistance of these mortars should be slightly improved. Considering the present results the mortars mechanical resistance improvement may be achieved through the formulation of mortars with higher clayish earth content, or alternatively, through the addition of natural fibers to mortars formulation, very common in this type of mortars. Both those options will be investigated in future research.